Di-n-butylbis(N-ethyl-N-phenyldithiocarbamato- kS)tin(IV). - Kamaludin, Nurul Farahana; Baba, Ibrahim; Awang, Normah; Mohamed Tahir, Mohamed Ibrahim; Tiekink, Edward R. T. (International Union of Crystallography, 2012)
The title compound, [Sn(C4H9)2(C9H10NS2)2], features a tetrahedrally coordinated SnIV atom; the dithiocarbamate ligands coordinate in a monodentate fashion, accompanied by two n-butyl chains. The non-coordinating thione S atoms are each proximate to the SnIV atom [3.0136 (7) and 2.9865 (8) Å], giving rise to distortions from the ideal geometry as evident in the wide C—Sn—C bond angle of 139.06 (12) °. In the crystal, C—H(...)S interactions lead to the formation of a linear supramolecular chain along the b axis. The chains are aligned into layers by C—H(...)π interactions, and the layers stack along [001]. One of the ethyl groups is statistically disordered over two sets of sites.